Diagnostic Value of Serum Procollagen III N-Terminal Peptide for Liver Fibrosis in Infantile Cholestasis - Wang, Yingcan; Pan, Weihua; Zhao, Dongying; Chen, Yan; Chen, Xuting; Xia, Hongping (Frontiers in Pediatrics, 2020)
BACKGROUND Several non-invasive markers have been reported as being effective for the assessment of fibrosis in adults with chronic viral hepatitis. The infantile liver is more susceptible to cholestasis, and it is important to promptly evaluate liver fibrosis to guide the clinical treatment. However, the clinical value of these markers in infants with cholestasis remains unknown. AIM To investigate the correlation between serum laminin (LN), hyaluronic acid (HA), procollagen III N-terminal peptide (PIIINP) level, and liver fibrosis stage in infants with cholestasis. METHODS One hundred and thirty-seven term infants with cholestasis were included. Laparoscopic exploration and cholangiography were performed to diagnose or rule out biliary atresia. Serum LN, HA, and PIIINP were measured prior to laparoscopic exploration. Liver biopsy was performed for all patients. Liver fibrosis was staged on a five-point scale (F0-F4) according to the METAVIR scoring system. The correlation between serum markers and liver fibrosis stage was assessed. A receiver operator characteristic analysis was performed to determine the accuracy of serum markers for predicting the liver fibrosis stage. RESULTS Serum PIIINP and HA were positively correlated with liver fibrosis stage (r = 0.622, P < 0.001 and r = 0.41, P < 0.001, respectively). There was no significant correlation between serum LN and liver fibrosis stage (P > 0.05). Serum aspartate aminotransferase, total bilirubin, direct bilirubin, and PIIINP were independently correlated with the fibrosis stage on multivariate ordinal regression analysis. Receiver operating curve (ROC) analysis showed that serum PIIINP was the most effective for the diagnosis of fibrosis grade. The area under the ROC curves (AUROCs) for serum PIIINP for diagnosing fibrosis stages ≥F1, ≥F2, ≥F3, and F4 (cirrhosis) were 0.843, 0.789, 0.82, and 0.891, respectively. The cut-off serum PIIINP value for predicting fibrosis stage ≥F1 was 242.3 ng/mL, with 73.8% sensitivity and 90% specificity. The cut-off value for predicting cirrhosis was 698.7 ng/mL, with 75% sensitivity and 96% specificity. CONCLUSION Serum PIIINP is a promising biomarker for predicting liver fibrosis stage, especially cirrhosis. Its assessment is a simple and noninvasive diagnostic method for liver fibrosis in infants with cholestasis.